K-Pop Fans Reading Anti-K-Pop: Religion, Identity, and Subjectivity - Okta Nurul Hidayati (Al'Adalah, 2025)
The expansion of K-pop fandom among young Muslim women in Indonesia has unfolded alongside the rise of digital da’wa that frames K-pop as a moral risk. This study examines how anti-K-pop da’wa texts construct the figure of the ideal Muslimah and how fans negotiate that framing in everyday practice. Using a qualitative-interpretive approach, Critical Discourse Analysis (CDA) of the book Pernah Tenggelam was combined with in-depth interviews with three Muslim women fans. The findings identify a configuration of nomination/predication/legitimation and intensification strategies that normalizes a binary opposition between the ideal Muslimah and the K-waver, which calls for identity repositioning. On the reception side, readers are not passive; they enact contextual moral reasoning through four tactics: content filtering, mapping private-public spaces, aesthetic reading (music/choreography rather than celebrity cult), and management of engagement intensity. These practices yield three dynamic subject positions: selective opposition, conditional co-existence, and hybridization, demonstrating the possibility of coexisting piety and popular pleasure. Conceptually, the study enriches scholarship on the encounter between popular culture and the politics of piety; methodologically, it demonstrates the integration of CDA with audience-reception data; and practically, it recommends dialogic-empathetic da’wa design and strengthened media literacy.